The added role of Doppler ultrasound evaluation of sickle cell disease vasculopathy as a state of arterial stiffness and decreased nitric oxide bioavailability - Marwa Mohammed Mohammed Onsy; Sonia Ali El-Saiedi; Douaa Mohammed Mohammed Elsheshtawy; Marwa Abd-Elhady Abd-Elsamad (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Sickle cell disease is an inherited hemoglobinopathy resulting in chronic hemolysis and painful vaso-occlusive crises. Sickle vasculopathy caused by impaired nitric oxide bioavailability and arterial stiffness and associated with multiple complications. Results Mean age of patients was 13.85 ± 2.53 SD, 50% were males, 77.5% were homozygous sickle cell disease (SS). Brachial artery parameters showed that baseline diameter was significantly higher (p < 0.001) and flow mediated dilatation (FMD) was significantly lower in patients than control (p < 0.001). Carotid artery parameters showed that carotid intima-media thickness (CIMT) and cross-sectional distensability were significantly higher in sickle group than control (p 0.001, p 0.007). Diastolic shear stress and elastic modulus showed no significant difference between sickle and control group (p 0.071, p 0.083). Regarding sickle subgroups, carotid intima-media thickness was higher and cross-sectional compliance and distensability were lower in subgroup II than subgroup I (p < 0.001, p < 0.018, p < 0.035), respectively. Conclusion Doppler assessment of brachial and carotid elastic properties may be helpful for early detection of sickle cell vasculopathy and sickle-related complications.